Dasypus hybridus (Cingulata: Dasypodidae) - Abba, Agustin Manuel (2016)
Dasypus hybridus (Desmarest, 1804) is commonly known as the southern long-nosed armadillo. Like all armadillos, it bears a carapace of ossified dermal scutes covered by epidermal scales. This diurnal species mainly inhabits grasslands on humic soils in Argentina, Uruguay, Paraguay, and southern Brazil. D. hybridus is omnivorous with a tendency to myrmecophagy and gives birth to 6-12 presumably genetically identical offspring. Listed as "Near Threatened" by the International Union for Conservation of Nature and Natural Resources, it is mainly threatened by habitat loss and hunting.